Synthesis of Lignin Nanoparticles: Top-Down and Bottom-Up Approaches - Rossella Grappa; Virginia Venezia; Brigida Silvestri; Aniello Costantini; Giuseppina Luciani (Medical Sciences Forum)
Lignin, a main byproduct from paper manufacturing and biorefineries, is now emerging as a new low-cost, renewable starting material for new product development. Its biocompatibility and safety make it valuable for creating novel and value-added products. Lignin, a polymer with many hydrophilic and active groups, confers many useful properties. However, there are several challenges to overcome due to its complex chemical structure and heterogeneous self-assembly behavior. Nanostructured systems using lignin could address these challenges, finding applications in food science, cosmetics, and healthcare. This study explores two main green synthesis approaches for lignin nanoparticles: bottom-up based on the self-assembly in a solvent–antisolvent system and top-down based on the ultrasonication. These nanoparticles are evaluated for morphology, estimation of phenolic content and antioxidant effects. Specifically, the antisolvent nanostructures show a spherical conformation with a higher antioxidant activity due to a better organization of phenolic hydroxyl groups. Obtained result have been exploited to draw an efficient and cheap technological route for lignin valorization.